2017
DOI: 10.1177/0011000017701820
|View full text |Cite
|
Sign up to set email alerts
|

College Women’s Subjective Femininity Stress, Gender Solidarity, and Psychological Help-Seeking Intentions

Abstract: Female gender has been consistently associated with positive psychological help-seeking attitudes and behaviors; however, surprisingly few empirical studies have examined how femininity-related variables impact women's help-seeking decision making. Informed by the theory of reasoned action (Ajzen & Fishbein, 1980), the purpose of this study was (a) to investigate the associations between two femininity constructs-subjective femininity stress and gender solidarity-and psychological help-seeking intention, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 48 publications
(87 reference statements)
0
12
0
Order By: Relevance
“…The finding that service characteristics and gender influenced cultural and mental health beliefs suggests that targeted stigma-reduction efforts to particular subgroups, including men, active duty and deployed veterans may be important. The difference observed on gender may be due to different socialization processes around vulnerability, social support and help-seeking (Judd, Komiti, & Jackson, 2008; Shea, Wong, Nguyen, & Baghdasarian, 2017), whereas the difference based on component and deployed status is likely due to acculturation, proximity and involvement with military culture.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that service characteristics and gender influenced cultural and mental health beliefs suggests that targeted stigma-reduction efforts to particular subgroups, including men, active duty and deployed veterans may be important. The difference observed on gender may be due to different socialization processes around vulnerability, social support and help-seeking (Judd, Komiti, & Jackson, 2008; Shea, Wong, Nguyen, & Baghdasarian, 2017), whereas the difference based on component and deployed status is likely due to acculturation, proximity and involvement with military culture.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, gender role socialization (i.e., men and women's gendered attitudes internalized from cultural norms and values; Addis & Mahalik, ) would be important to examine in the behavioral healthcare context. Adherence to both traditional masculine (Hammer, Vogel, & Heimerdinger‐Edwards, ) and feminine norms (Shea et al, ) can influence help‐seeking behaviors, but it is unclear how these internalized norms may influence referral adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Self-stigma of seeking help (i.e., internalized beliefs that one is inadequate if one seeks professional help) has been identified as a significant barrier to women’s psychological help seeking (Shea et al, 2017; Vogel et al, 2006), likely due to its pernicious effects on attitudes and PBC. Research into women’s intention to seek individual psychotherapy demonstrated that self-stigma has a negative relationship with attitudes toward psychotherapy (Shea et al, 2017). Past couple help-seeking studies have also supported a negative association between self-stigma and attitudes in men (Spiker et al, 2019), thus we anticipated this association for women as well.…”
Section: Tpb and Couple Help Seekingmentioning
confidence: 99%
“…The limited research into women’s perceptions of individual psychotherapy suggests these relational schemas matter when deciding upon the need for psychotherapy. For example, prior research has shown that subjective feminine stress has a direct, negative association with women’s intent to seek individual psychotherapy (Shea et al, 2017). Women have also noted that they avoid seeking help because they have “to be mother, sister, mother, spouse, so, I’m there for everyone else but I’m not there for myself” (Ishikawa et al, 2010, p. 7).…”
Section: Women’s Relational Schemas and Couple Help Seekingmentioning
confidence: 99%